2016
DOI: 10.1016/j.lwt.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-producing ability and tolerance to industrial sanitizers in Salmonella spp. isolated from Brazilian poultry processing plants

Abstract: The aims of this study were to analyze the biofilm-producing ability of 98 strains isolated from different surface materials in poultry cutting rooms; to assess the presence of the most important to Salmonella biofilm formation genes adrA and csgD in these strains; and to evaluate the tolerance biofilms formed in polypropylene and polyurethane slides to sanitizers commonly used in the industry. Viable cells were removed from the slides soon after treatment with sanitizers, and then submitted to reincubation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
2
18
0
5
Order By: Relevance
“…Ziech et al (2016a) reported that 100% of Salmonella sp. strains isolated in poultry slaughterhouses and processing plants in Brazil were able to produce biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…Ziech et al (2016a) reported that 100% of Salmonella sp. strains isolated in poultry slaughterhouses and processing plants in Brazil were able to produce biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…The chemicals currently used in the disinfection processes belong to the following types: acidic compounds, biocides, aldehydebased disinfectants, caustics, chlorine, hydrogen peroxide, iodine, isothiazolinones, ozone, peracetic acid, phenols, biguanides, and surfactants (Simões, Simões, Machado, Pereira, & Vieira, 2006;Bremer, Fillery, & McQuillan, 2006). Ziech et al (2016) reported that treatment with peracetic acid was not considered efficient to eliminate biofilms formed in polypropylene and polyurethane. Recently, Sarjit & Dykes (2017) reported that trisodium phosphate was more effective against biofilms than sodium hypochlorite and has strong potential as a sanitizer to reduce biofilm formation by Salmonella spp.…”
Section: Disinfectantsmentioning
confidence: 99%
“…Identify genes associated with apoptosis (avrA), oxidative stress (sodC), invasion (invA), adhesion and bio lm (agfA, sefA and lpfA) and quorum sensing (luxS) [15,39,6] helps to characterize the pathogenic potential and to understand the strategies for perpetuation in the environment. At the same time, among the hypotheses that may explain S. Minnesota persistence in the environment, its ability to form bio lms stands out, which hinders its control in the food industry [46]. In this condition microorganisms have different responses to heat treatments, biocides and antimicrobials, and are therefore a constant source of contamination [18,27,40].…”
Section: Introductionmentioning
confidence: 99%